Non-invasive hemodynamic monitoring and cardiac preload assessment in severely injured children in the emergency department - Jing Chen; Jia Li; Xingpeng Wang; Kai Ma; Jie Xu; Huifang Zhang; Yufei Su; Hua Li (BMC Emergency Medicine)
Abstract Objectives This study aimed to evaluate cardiac preload and identify early predictors of severe trauma in pediatric patients using non-invasive hemodynamic monitoring in the pediatric emergency department. Methods A prospective cohort study was conducted at Xi’an Children’s Hospital (June 2022–October 2024) with 167 patients, divided into mild (84) and severe (83) trauma groups. Non-invasive monitoring began shortly after admission, collecting parameters alongside clinical and laboratory assessments. Results No significant differences in demographics or injury characteristics were found between groups. The severe trauma group had higher blood transfusion requirements (TAR) (p < 0.01). Hemodynamic parameters showed reduced pre-ejection period (PEP), left ventricular ejection time, and thoracic fluid content (t = 5.655, z = -4.368, z = -3.702; p < 0.01), indicating insufficient preload. Elevated heart rate (t = -4.127; p < 0.01) compensated for this. Reduced stroke volume index (t = 2.339, p < 0.05) and higher cardiac index (z = -1.979; p < 0.05) suggested compensation for low hemoglobin. The severe group also had elevated white blood cells, blood glucose, lactate, interleukin-6, interleukin-10, ALT, and AST (p < 0.01), while hemoglobin, fibrinogen, and albumin were decreased (p < 0.01). Logistic regression identified PEP, albumin, interleukin-6, and TAR as independent risk factors for severe trauma (p < 0.05). PEP and interleukin-6 had the highest area under the curve values (> 0.70). Conclusions Non-invasive hemodynamic monitoring can detect early signs of insufficient preload in severe pediatric trauma, and the combination of PEP and interleukin-6 aids in severity assessment and clinical decision-making. Clinical trial registration Not applicable.